The adaptive cycle: More than a metaphor - Sundstrom, Shana M.; Allen, Craig R. (Ecological complexity, 2019)
•Adaptive cycles reflect endogenous dynamics fundamental to complex adaptive systems.•A suite of thermodynamic indicators exist to quantify adaptive cycles.•Measuring adaptive cycles at all scales in a panarchy an important step forward. The adaptive cycle and its extension to panarchy (nested adaptive cycles) has been a useful metaphor and conceptual model for understanding long-term dynamics of change in ecological and social–ecological systems. We argue that adaptive cycles are ubiquitous in complex adaptive systems because they reflect endogenously generated dynamics as a result of processes of self-organization and evolution. We synthesize work from a wide array of fields to support this claim. If dynamics of growth, conservation, collapse and renewal are endogenous dynamics of complex adaptive systems, then there ought to be signals of system change over time that reflect this. We describe a series of largely thermodynamically based indicators that have been developed for this purpose, and we add a critical and heretofore missing component–namely, that of understanding dynamics of change (adaptive cycles) at objectively identified spatial and temporal scales nested within each system, instead of solely at the system level. The explicit consideration of scales, when coupled with selective indicators, may circumvent the need for multiple indicators to capture system dynamics and will provide a richer picture of system trajectory than that offered by a single-scale analysis. We describe feasible ways in which researchers could systematically and quantitatively look for signatures of adaptive cycle dynamics at scales within ecosystems, rather than relying on metaphor and largely qualitative descriptions.